2018
DOI: 10.1186/s12958-018-0368-4
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous leptin affects sperm parameters and impairs blood testis barrier integrity in adult male mice

Abstract: BackgroundSerum leptin levels are augmented in obese infertile men and in men with azoospermia. They also correlate inversely with sperm concentration, motility and normal forms. The mechanisms underlying the adverse effects of excess leptin on male reproductive function remain unclear. The present study aimed to evaluate the effects of exogenous leptin on sperm parameters in mice and to explore the underlying mechanisms.MethodsWe treated normal adult male mice with saline, 0.1, 0.5 or 3 mg/kg leptin daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 51 publications
3
20
0
2
Order By: Relevance
“…Studies on Sprague‐Dawley rats treated with 60 μg/kg body weight of leptin for either 6 or 2 weeks also came to the same conclusions (Almabhouh et al, ; Md Mokhtar et al, ). Similar response was also noted in mice recently when given exogenous leptin, although the doses ranging from 0.5 to 3.0 mg/Kg body used in this study were much higher than those used in Sprague‐Dawley rats (Wang, Zhang, Hu, & Li, ). While the precise mechanism responsible for these leptin‐induced effects on spermatozoa and seminiferous tubules remains uncertain, leptin‐induced increase in free radical production (ROS) is however implicated (Abbasihormozi et al, ).…”
Section: Leptin and Male Infertilitysupporting
confidence: 85%
See 2 more Smart Citations
“…Studies on Sprague‐Dawley rats treated with 60 μg/kg body weight of leptin for either 6 or 2 weeks also came to the same conclusions (Almabhouh et al, ; Md Mokhtar et al, ). Similar response was also noted in mice recently when given exogenous leptin, although the doses ranging from 0.5 to 3.0 mg/Kg body used in this study were much higher than those used in Sprague‐Dawley rats (Wang, Zhang, Hu, & Li, ). While the precise mechanism responsible for these leptin‐induced effects on spermatozoa and seminiferous tubules remains uncertain, leptin‐induced increase in free radical production (ROS) is however implicated (Abbasihormozi et al, ).…”
Section: Leptin and Male Infertilitysupporting
confidence: 85%
“…In general, it appears that oxidative stress following leptin treatment is responsible for the increased apoptosis of spermatozoa and seminiferous tubular cells, which might then be responsible for the decreased sperm concentration (Almabhouh et al, ; Wang et al, ). In fact, this might have also contributed to the leptin‐induced decreases in height and diameter of seminiferous tubules and sperm count reported recently in Sprague‐Dawley (Haron et al, ; Md Mokhtar et al, ).…”
Section: Mechanisms Of Leptin‐induced Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the absence of endogenous leptin is associated with hypogonadism, 53,54 yet, high leptin level is reported to suppress steroidogenesis 54 . Human and experimental studies have linked significant decline in testosterone level, impairment in sperm count and motility, and increases in sperm abnormal morphology and DNA fragmentation, with high leptin levels 55‐57 . In fact, experiments demonstrated that exogenous leptin administration impacted negatively on sperm parameters in rats, 58,59 thus raising concerns about leptin levels in subfertile/infertile obese men.…”
Section: Discussionmentioning
confidence: 99%
“…It also has a direct local effect on leydig and sertoli cell function (Lampiao, Agarwal, & du Plessis, ). Serum leptin levels have been found to be high in most obese people and rodents with high‐fat diet ingestion for a long term (Wang, Zhang, Hu, & Li, ).…”
Section: Introductionmentioning
confidence: 99%